Teaching Vocabulary through Fly Swatter Game - Hikmah Noerqori Saputra; Muhamad Sofian Hadi (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2019)
The study aimed to find out whether fly swatter game can give influence toward students’ vocabulary mastery. The subject of this study was grade VII-2 of SMPN 9 Tangerang Selatan in the academic year of 2018/2019, which consisted of 42 students. The method used in this study is a quantitative method with the design of the pre-experimental study. The data from pre-test and post-test were analyzed statistically using spss 16. The result of this study showed; the students’ pre-test mean score was 45.4 and the students’ post-test mean score was 86.6. The result of t-test was 21.55 and significant (2-tailed) was 0.00 < p (0.05). The hypothesis (H1) was accepted, which means there is a significant difference between pre-test and post-test scores of the experimental group. It can be concluded that applying fly swatter game in teaching vocabulary to 7th grade students of SMPN 9 Tangerang Selatan is effective.